In Vitro Activity of Imipenem-Relebactam, Meropenem-Vaborbactam, Ceftazidime-Avibactam and Comparators on Carbapenem-Resistant Non-Carbapenemase-Producing Enterobacterales - Rémy A. Bonnin; Sandrine Bernabeu; Cécile Emeraud; Thierry Naas; Delphine Girlich; Agnès B. Jousset; Laurent Dortet (MDPI AG, 2023)
Background: Avibactam, relebactam and vaborbactam are β-lactamase inhibitors that proved their efficiency against KPC-producing Enterobacterales. Regarding their inhibitor activity towards Ambler's class A extended spectrum β-lactamases (ESBL) and Ambler's class C cephalosporinase (AmpC), they should be active on most of the carbapenem-resistant non-carbapenemase-producing Enterobacterales (CR non-CPE). Objectives: Determine the in vitro activity of ceftazidime-avibactam, imipenem-relebactam and meropenem-vaborbactam and comparators against CR non-CPE. Methods: MICs to ceftazidime/avibactam, imipenem/relebactam, meropenem/vaborbactam, but also temocillin, ceftolozane/tazobactam, ertapenem, colistin, eravacycline and tigecycline were determined by broth microdilution (ThermoFisher) on a collection of 284 CR non-CPE (inhibition zone diameter < 22 mm to meropenem). Whole genome sequencing was performed on 90 isolates to assess the genetic diversity as well as resistome. Results: According to EUCAST breakpoints, susceptibility rates of ceftazidime, imipenem, meropenem and ertapenem used at standard dose were 0.7%, 45.1%, 14.8% and 2.5%, respectively. Increased exposure of ceftazidime, imipenem and meropenem led to reach 3.5%, 68.3% and 67.7% susceptibility, respectively. Using the EUCAST clinical breakpoints, susceptibility rates of ceftazidime/avibactam, imipenem/relebactam and meropenem/vaborbactam were 88.4%, 81.0% and 80.6%, respectively. Susceptibility rates of temocillin, ceftolozane/tazobactam, tigecycline, eravacycline, and colistin were 0%, 4.6%, 27.8%, 54.9% and 90.1%. MICs distributions with and without the presence of the inhibitor demonstrated a better ability of avibactam and relebactam compared to vaborbactam to restore susceptibility to the associated β-lactam. Conclusions: This study demonstrated the in vitro efficacy of ceftazidime/avibactam, imipenem/relebactam and to a lesser extent meropenem/vaborbactam against CR non-CPE. Moreover, to test all β-lactams/β-lactamases inhibitors combinations without a priori for CRE, non-CPE is crucial since resistance to one of the β-lactam/β-lactamase inhibitor combinations does not predict resistance to another molecule, depending on the resistance mechanisms involved.